The haunted and the haunter: a study of memory and detachment in the poetry of Thomas Hardy - Berkman, Karin Fran (My University, 2015)
The image of a haunting is of particular significance in the poetry of Thomas Hardy. As metaphor for the workings of memory it fills Hardy's need for an image which captures the intensity of recall he experiences, and which cannot be described simply in the image of remembering. The image of a haunting Is at times implicit in poems concerned with the recreation of the past. The sense we have in these poems of memory summonsing the past, and its consequent materialization, the assumption of immediate form, distinguishes these poems from those in which a conventional memory is recorded, where the past is simply described rather than recreated. The haunting is used explicitly to accommodate Hardy's sensitivity to the lingering presence of past experience which expresses itself in repeated images of shadowy phantoms , presences which seem to edge into the poet's present experience and in the multiplicity of actual ghosts dramatically re- enacting the scenes of the past. By associating the experience of remembering with a haunting Hardy transforms the recall of the past, into a dramatic event, in which the self actively confronts his past and is allowed to visualize, hear and address the dead. The image is expressive of Hardy's profound nostalgia for a past which is perceived as affording placement and familiarity to a self unhoused and estranged in a present which bars comprehension and the perception of significance. in a haunting the self is allowed a rehearsal of the past equipped with understanding and vision. In an examination of the 1912-1913 poems, the centrality of the haunting image to the sequence is considered. The image of the haunting functions as antidote to the burdens of transience and mortality? in the haunting the pain of estrangement can be allayed and the reality and finality of death can be momentarily annexed. In the 1912-1913 poems the haunting is the medium for an expression of regret and atonement, a mode of expiation. Finally, the dissertation studies the assumption of ghost hood by Hardy's personae and considers the appositeness of the image of the poet as haunter in expressing the self's tendency to withdrawal and self effacement. The equation of the self with a ghost is expressive of the self's sense of exclusion from a welcoming' community, its retreat from the press of experience, but also of the self's unwilling immersion in the past and consequent inability to maintain a firm grip on its identity. The complexity of the haunted and haunter images accommodates Hardy's sense of the complexities of memory and identity, concerns to which the poems return repeatedly as the focus of exploration.